Áreas com potenciais para regeneração de atributos do solo no norte maranhense - Veras, Carlos Magno dos Anjos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In the fallow system, the soil is left undisturbed for a very variable period of time so that the pool of soil organic matter recovers and resembles that found in adjacent mature forests. To prove this practice was carried out a survey in the town of Quilombo Damásio, City of Guimaraes, Maranhao State where soil samples were obtained in fallow areas 25, 20, 15, 10, and five years; the current cultivated area (farming) and other primary forest (control) in the layers 0-20 and 20 to 40 cm. The fallow system at both depths and times, showed increases and macronutrient losses. For the statistical analysis we observed significant differences in contributions and loss of nutrients between treatments (fallow times) in both soil depths analyzed. The correlation analysis showed a positive association and negative for respondents macronutrients (P, K+, Ca2+ and Mg2+). Over time the fallow system was efficient in the recovery of natural soil fertility

No sistema de pousio, o solo é deixado em repouso por um período de tempo muito variável para que o pool de matéria orgânica do solo se recupere e se assemelhe ao encontrado em florestas maduras adjacentes. Para comprovar tal prática foi realizada uma prospecção no Povoado Quilombo de Damásio, Município de Guimarães, Estado do Maranhão onde obteve-se amostras do solo em áreas de pousio com 25, 20, 15, 10, e 5 anos; da área atual cultivada (lavoura) e outra de floresta primária (controle) nas camadas de 0 a 20 e 20 a 40 cm. O sistema de pousio, nas duas profundidades e tempos, apresentou aumentos e perdas de macronutrientes. Pela análise estatística observou-se diferenças significativas nos aportes e perdas de macronutrientes entre os tratamentos (tempos de pousios) nas duas profundidades do solo analisadas. A análise de correlação apresentou associação positiva e negativa para os macronutrientes pesquisados (P, K+, Ca2+ e Mg2+). Ao longo do tempo o sistema de pousio mostrou-se eficiente na recuperação da fertilidade natural do solo
Keywords: Solos - Analise; Agricultura; Corte; Solos - Fertilidade; Nutrientes; Soil science